Pengaruh Investment Knowledge, Modal Investasi Dan Kemajuan Teknologi Informasi Terhadap Minat Investasi - Ni Kadek Pradnyanita Utami; I Wayan Sudiana; I Putu Deddy Samtika Putra (Hita Akuntansi dan Keuangan, 2022)
Financial management is basically an important stage for a person. Good financial management will help individuals free from the trap of possible poverty. Based on this basis, this paper was made, revealing the relationship between investment knowledge, minimum investment capital, and advances in information technology on student investment interest in the capital market. 448 student from the accounting department of UNHI were use as the research population where 82 people were selected as research samples whose data will be tested using multiple regression technique. Various research processes have been carried out and the final result reveal the fact that for students majoring in accounting. Their investment interest can be increased along with increasing selft-knowledge in the investment field, capital that is relatively in accordance with their limited finances and the convenience of available technology.